Visible Light-Driven Radical-Mediated C–C Bond Cleavage/Functionalization in Organic Synthesis - Yu, Xiao-Ye; Chen, Jia-Rong; Xiao, Wen-Jing (Chemical reviews, 2021)
Thermal C-C bond cleavage reactions allow the construction of structurally diverse molecular skeletons via predictable and efficient bond reorganizations. Visible light photoredox-catalyzed radical-mediated C-C bond cleavage reactions have recently emerged as a powerful alternative method for overcoming the thermodynamic and kinetic barrier of C-C bond cleavage in diverse molecular scaffolds. In recent years, a plethora of elegant and useful reactions have been invented, and the products are sometimes otherwise inaccessible by classic thermal reactions. Considering the great influence and synthetic potential of these reactions, we provide a summary of the state of art visible light-driven radical-mediated C-C bond cleavage/functionalization strategies with a specific emphasis on the working models. We hoped that this review will be useful for medicinal and synthetic organic chemists and will inspire further reaction development in this interesting area.